2013
DOI: 10.5194/bg-10-5671-2013
|View full text |Cite
|
Sign up to set email alerts
|

Respiration of Mediterranean cold-water corals is not affected by ocean acidification as projected for the end of the century

Abstract: The rise of CO2 has been identified as a major threat to life in the ocean. About one-third of the anthropogenic CO2 produced in the last 200 yr has been taken up by the ocean, leading to ocean acidification. Surface seawater pH is projected to decrease by about 0.4 units between the pre-industrial revolution and 2100. The branching cold-water corals Madrepora oculata and Lophelia pertusa are important, habitat-forming species in the deep Mediterranean Sea. Although previous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 41 publications
9
33
1
Order By: Relevance
“…It would therefore be worthwhile to measure the metabolic rate of the corals under long-term influence of ocean acidification and warming in order to see if the increased costs of mineralisation are reflecting in enhanced respiration for instance. In two mid-and longterm studies, respiration rates did not significantly change with elevated pCO 2 levels compared to ambient levels (Maier et al, 2013b;Hennige et al, 2015), while a significant decline was found after short-term exposure to acidified conditions (3 weeks at 750 µatm) (Hennige et al, 2014). Elevated temperature by 2 • C led to a 50% increase in respiration rates of L. pertusa (Dodds et al, 2007), but combined long-term exposure of elevated temperature and CO 2 concentration did not result in significant changes (Hennige et al, 2015).…”
Section: Growth Ratesmentioning
confidence: 84%
See 1 more Smart Citation
“…It would therefore be worthwhile to measure the metabolic rate of the corals under long-term influence of ocean acidification and warming in order to see if the increased costs of mineralisation are reflecting in enhanced respiration for instance. In two mid-and longterm studies, respiration rates did not significantly change with elevated pCO 2 levels compared to ambient levels (Maier et al, 2013b;Hennige et al, 2015), while a significant decline was found after short-term exposure to acidified conditions (3 weeks at 750 µatm) (Hennige et al, 2014). Elevated temperature by 2 • C led to a 50% increase in respiration rates of L. pertusa (Dodds et al, 2007), but combined long-term exposure of elevated temperature and CO 2 concentration did not result in significant changes (Hennige et al, 2015).…”
Section: Growth Ratesmentioning
confidence: 84%
“…We aimed at identifying how differently L. pertusa reacts towards multiple climate change stressors when fed with a higher amount of zooplankton food compared to 10-fold lower food availability. It was suggested that calcification rates might be maintained under an acidified environment via mobilising lipid reserves from the coral's tissue (Maier et al, 2013b;Hennige et al, 2014), but this source of stored energy is bound to decline on longer time scales. Furthermore, elevated temperatures might lead to increased metabolic rates (Dodds et al, 2007) that require additional energetic input.…”
Section: Introductionmentioning
confidence: 99%
“…The natural fluctuations in the physicochemical conditions (including oxygen, carbon, nutrients and food supply), driven by large hydrodynamics, may provide flexibility for these organisms, giving them increased adaptation potential for surviving a range of conditions, as has been found with warm-water corals and temperature34. This naturally fluctuating environment could help to explain the high levels of variability found in CWCs ocean acidification experiments, especially as several recent laboratory experiments CWCs are able to continue calcifying under high CO 2 , low Ω Aragonite conditions [e.g 353637…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental work has revealed considerable variation in the physiological response of cold‐water corals to ocean acidification (Maier et al . , , ,b; Form & Riebesell ; Hennige et al . ; Lunden et al .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a recent 3‐month study on both L. pertusa and M. oculata found no significant change in either respiration or calcification rates even with CO 2 concentrations as high as 1000 ppm (pH of approximately 7.73; Maier et al . ,b). Calcification, skeletal density and energy reserves in Dendrophyllia cornigera did not change significantly during a 314‐day acidification experiment with pH values as low as 7.81; however, in the same study, Desmophyllim dianthus exhibited a significant, 70% reduction in calcification (Movilla et al .…”
Section: Introductionmentioning
confidence: 99%